Results on Difference Analogues of Valiron-Mohon'ko Theorem - Ran Ran Zhang; Zhi Bo Huang (Abstract and Applied Analysis)
The classical Valiron-Mohon'ko theorem has many applications in the study of complex equations. In this paper, we investigate rational functions in f(z) and the shifts of f(z). We get some results on their characteristic functions. These results may be viewed as difference analogues of Valiron-Mohon'ko theorem.